2012
DOI: 10.1002/cctc.201200080
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene (NHC) Catalyzed Cycloaddition of CO2 to N‐Tosyl Aziridines: Regio and Stereoselective Synthesis of Oxazolidin‐2‐ones

Abstract: NHC pumping on your stereo: A general N‐heterocyclic carbene (NHC) catalyzed methodology for insertion of CO2 into N‐tosyl aziridines giving 3,5‐disubstituted and 3,4,5‐trisubstituted oxazolidin‐2‐ones is developed. This method is also applied for the stereoselective synthesis of (4R,5R)‐4‐methyl‐5‐phenyloxazolidin‐2‐one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…N-Heterocyclic carbene (NHC) 283-catalyzed highly regio-and stereoselective carboxylation of N-tosylaziridines 10 with CO 2 leads to the formation of 3,5-disubstituted and 3,4,5-trisubstituted oxazolidin-2-ones (284 and 285) in good yields [129]. It has also been observed that the insertion of CO 2 in 2-alkyl-Ntosylaziridine is possible to produce oxazolidinone compound without any catalyst, solvent, high temperature, or pressure, when high-speed ball milling has been applied (Scheme 72) [130].…”
Section: Synthesis Of Oxazolidines Oxazolines and Oxazolesmentioning
confidence: 99%
“…N-Heterocyclic carbene (NHC) 283-catalyzed highly regio-and stereoselective carboxylation of N-tosylaziridines 10 with CO 2 leads to the formation of 3,5-disubstituted and 3,4,5-trisubstituted oxazolidin-2-ones (284 and 285) in good yields [129]. It has also been observed that the insertion of CO 2 in 2-alkyl-Ntosylaziridine is possible to produce oxazolidinone compound without any catalyst, solvent, high temperature, or pressure, when high-speed ball milling has been applied (Scheme 72) [130].…”
Section: Synthesis Of Oxazolidines Oxazolines and Oxazolesmentioning
confidence: 99%
“…(45-1)]. [261] The application of this methodology for the stereoselective synthesis of (4R,5R)-4-methyl-5-phenyloxazolidin-2-one, a well-known chiral auxiliary, was also demonstrated [Eq. ].…”
Section: Cycloaddition Of Epoxides Catalyzed By Nhc-co 2 Adductsmentioning
confidence: 99%
“…Chirality transfer from enantiopure aziridines provides enantioenriched products. 35,54 This transformation can give two different isomers (Scheme 18), but ionic liquids, 81 NHCs, 82 Cr-salen, 83 and Alsalen/ammonium salt, 35 favour the 5-substituted isomer (if the nitrogen is substituted and R ' = Ph).…”
mentioning
confidence: 99%